THE TEACHING STYLES HAVE BY THE ENGLISH TEACHERS IN SMP NEGERI 27 BUTON TENGAH - Ary Irjayanti Herman (English Education Journal, 2023)
The objectives of this study was to find out the teaching style of teachers at SMP Negeri 27 Buton Tengah. The type of this research used qualitative research. Then to the design used by case studies research. It use several methods, such as interviews and observations to collect the data. The location of the research was at SMP Negeri 27 Buton Tengah. This research was precisely location in Madongka Village, Lakudo, Buton Tengah. The subject of this research was an English teacher at second grade of SMP Negeri 27 Buton Tengah.The instrument in this research process was the researcher herself who acts as the research instrument. To analyze the data from observation and interviews, researchers used Data collection, Data reduction, and data display. The result of the finding indicated that the types of teaching style used by English teacher at SMPN 27 Baton Tengah namely Expert style, formal authority style, Personal model or demonstrator and facilitator style. The dominant teaching style used by the teacher was formal auditory style, personal model or demonstrator. The teacher usually design group activities that require active learning, student to student’s collaboration, and problem solving.